Circularly Polarized Antenna System for the Quality Evaluation Application of Apple Fruit - M. Flashy, Angeline; G.P. , Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the Omnidirectional Circularly Polarized Antenna for the quality assessment applications of Apple samples. The compact rectangular 2x2 antenna array is designed with a bandpass filter for the triple-band microwave sensing at 2.4/3.5/5.8 GHz. The microstrip antenna senses the spectrum of the signal produced from the apple sample for quality evaluation. The antenna comprises back-to-back microstrip patches fed by a 50-ohm impedance matching. A frequency ratio for the antenna design is achieved greater than 3 dB, which can be tuned for triple frequencies. An analysis of omnidirectional circular polarization mechanism, gain, directivity, efficiency, and radiated power vs. frequency, radiation intensity vs. magnitude of microstrip patch antenna, as well as the triple-band operation, is achieved with numerical and experimental data. The proposed omnidirectional circularly polarized antenna provides 15 dB for triple frequency bands.